Faith Education in the Prophet Muhammad SAW: An Analytical Study of Q.S. Al-Imran: 159 and Q.S. At-Taubah: 128-129 - Arinah Arinah; Alimudin Alimudin (Jurnal test, 2023)
This research is based on the importance of moral education and the lack of research that discusses the moral education of the Prophet Muhammad SAW from the perspective of the Qur'an. The purpose of this research is to find out how the education of faith in the Prophet Muhammad SAW from the perspective of Al-Qur'an Surah Al-Imran: 159 and Surah At-Taubah: 128-129. The method used in this research is library research using an interpretation approach. The data sources used are primary data sources and secondary data sources. The primary data source is obtained from the Al-Qur'an, while this secondary source is the second source that supports the primary data source, namely the source contained in the hadith of the commentary. In addition, the author also uses Al-Qur'an references, books, articles, magazines, and so on, as well as from educational figures, whose material is related to the education of faith in the Prophet Muhammad SAW. The results of this study indicate that faith education in the Prophet Muhammad SAW is very important in forming good character and personality for Muslims. Taking an example from his morals and attitudes, as well as practicing forgiveness, patience, deliberation, and trusting Allah, helps create harmonious relationships with fellow human beings and earns the pleasure of Allah SWT.